Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 3 - Section 3.5 - Determinants and Cramer’s Rule - Exercise Set - Page 240: 14


$(x,y)=(-1,-3)$; dependent equation

Work Step by Step

Need to apply Cramer's Rule. $x=\dfrac{D_x}{D}$; $y=\dfrac{D_y}{D}$ Now, $D=\begin{vmatrix}1&5\\-2&-1\end{vmatrix}=-1+10=9$; $D_x=\begin{vmatrix}5&-2\\-2&-1\end{vmatrix}=-5-4=-9$ $D_y=\begin{vmatrix}1&5\\5&-2\end{vmatrix}=-2-25=-27$ Thus, $x=\dfrac{-9}{9}=-1$ and $y=\dfrac{-27}{9}=-3$ Hence, $(x,y)=(-1,-3)$; dependent equation
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.